2015
DOI: 10.1007/s13277-015-4401-3
|View full text |Cite
|
Sign up to set email alerts
|

GSTT1 and GSTM1 polymorphisms predict treatment outcome for breast cancer: a systematic review and meta-analysis

Abstract: Observational studies have reported controversial results on the association between GSTT1 and GSTM1 genotypes and treatment outcome of breast cancer. The purpose of this study is to evaluate the association between GSTT1 and GSTM1 and treatment outcome in breast cancer patients. Eligible studies were searched in PubMed, EMBASE, Cochrane Library, and China National Knowledge Infrastructure databases. A random-effect model or fixed-effect model was used to calculate the overall combined risk estimates. Twenty-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…41 The frequencies of hematological toxicities, such as anemia, leukopenia, neutropenia, and thrombocytopenia, were variable in previous studies. 4,14,[17][18][19]26,27,41,42 The poor tolerance of thrombocytopenia (grade 1-above) differs from the other hematological toxicities because it was classified according to platelet counts < 75,000/mm 3 and literature. 19,42,43 Perhaps different frequencies of hematological toxicities are related to the timing of blood sample collection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…41 The frequencies of hematological toxicities, such as anemia, leukopenia, neutropenia, and thrombocytopenia, were variable in previous studies. 4,14,[17][18][19]26,27,41,42 The poor tolerance of thrombocytopenia (grade 1-above) differs from the other hematological toxicities because it was classified according to platelet counts < 75,000/mm 3 and literature. 19,42,43 Perhaps different frequencies of hematological toxicities are related to the timing of blood sample collection.…”
Section: Discussionmentioning
confidence: 99%
“…19,42,43 Perhaps different frequencies of hematological toxicities are related to the timing of blood sample collection. 14,41 In our study, hematological toxicity was scored based on samples collected before each cycle of chemotherapy (about 21 days) to determine the recovery of red blood cells, neutrophils, and platelets. Previous studies have demonstrated the association between chemotherapy-related severe anemia and thrombocytopenia and the GSTP1 c.313A>G polymorphism in patients who received carboplatin and paclitaxel-based chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their main focus was on circulating tumor cells, which contributed better prognostic information than CA 15-3. Other innovative markers are also of considerable interest [ 20-23 ]. However, none of these are part of routine clinical practice yet.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, GSTM1 and GSTT1 polymorphisms might be associated with renal cell carcinoma risk or treatment outcomes of breast cancer 48,4951.…”
Section: Discussionmentioning
confidence: 99%